The Ethics of Narrative Essays on History, Literature, and Theory, 1998-2007. - White, Hayden (Cornell University Press, 2022)
"The first in a two-volume anthology of Hayden White's uncollected essays from the last two decades of his life, revealing White as a public intellectual. It places White's thought in context, explaining its major themes, sources, and frames of reference, and features five previously unpublished lectures as well as more complete versions of several published essays"--